Subversi Naratif Paulus di Areopagus (Kisah Para Rasul 17:22–31): Kerangka Apologetika Kontekstual untuk Era Digital - Paraso, Srifika; Juanta, Elkria (Vieka Wahana Semesta, 2025)
The pluralist digital age presents a fundamental challenge to Christian apologetics, demanding a model that goes beyond traditional propositional argumentation. The epistemological environment of the internet, characterized by a thirst for novelty, flat authority, and fragmented personal narratives, often renders classical apologetic approaches ineffective. This study aims to construct a contextually relevant model of apologetics by performing a narrative exegesis of Paul's speech on the Areopagus in Acts 17:22–31. Using a qualitative method based on narrative criticism, this study analyzes the rhetorical and theological strategies used by Paul as described by Luke. The results of the study show that Paul did not simply accommodate or confront Hellenistic philosophy, but applied the strategy of